2017
DOI: 10.4067/s0370-41062017000500006
|View full text |Cite
|
Sign up to set email alerts
|

Capacidad vesical funcional mediante ultrasonido en pacientes con enuresis primaria monosintomática

Abstract: ResumenIntroducción: La enuresis primaria monosintomática es un problema clínico común que afecta del 5 al 10% de los niños en edad escolar. La etiología exacta no se conoce, pero se ha propuesto una capacidad vesical funcional disminuida como factor predisponente. Existen pocos reportes en la literatura del uso de ultrasonido para su evaluación. Objetivo: Determinar si la capacidad vesical funcional medida por ultrasonido está disminuida en enuresis primaria monosintomática comparada con población sana. Pacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…10 Several studies have shown that FBC is reduced by up to 50% in children with NE. 15 According to Kim,46.5% of all patients had reduced FBC for age, and this was similar to other studies (30-50%). 16 However, Acosta et al reported that 85% of patients with NE showed an MVV value less than 70% of the EBC value.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…10 Several studies have shown that FBC is reduced by up to 50% in children with NE. 15 According to Kim,46.5% of all patients had reduced FBC for age, and this was similar to other studies (30-50%). 16 However, Acosta et al reported that 85% of patients with NE showed an MVV value less than 70% of the EBC value.…”
Section: Discussionsupporting
confidence: 87%
“…16 However, Acosta et al reported that 85% of patients with NE showed an MVV value less than 70% of the EBC value. 15 This is probably because the lower limit of the normal range is set at 70%. In the present study, 68-70% (according to the measurement methods, MVV vs UFM) of total patients had a small FBC for age, regardless of the NE subgroup.…”
Section: Discussionmentioning
confidence: 99%